2020
DOI: 10.1002/agg2.20069
|View full text |Cite
|
Sign up to set email alerts
|

Drought‐tolerant transcription factors identified inArachis dardaniandArachis ipaënsis

Abstract: In this study, a greenhouse transcriptome study with 7‐d‐imposed drought was conducted on Arachis dardani Krapov. & W.C. Greg. (GK 12946) and the reference species A. ipaënsis (Krapov. and W.C. Greg.) (K 30076) (B genome donor of the cultivated peanut) to identify candidate genes associated with drought. Differential gene expression analysis (EdgeR Test) of the normalized reads per kilobase million (RPKM) values was conducted with a fold value ≥ |2| at the P ≤ .05 level using CLC Genomics Workbench v8.1. Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Wild groundnut species genes that are drought stress involved are discriminated into two groups: (i) genes that are plant cell protectors and act as upstream regulators and (ii) regulatory genes, such as transcription factors, implicated in the ABA pathways [ 146 ]. Tolerance to abiotic stresses has been recorded in A. stenosperma [ 128 ], while Guimarães et al [ 147 ] identified a remarkable number of transcription factors and genes related to drought stress in a peanut ancestor, A. duranencis .…”
Section: The Exploitation Of the Cwrs In Specific Cultivated Speciesmentioning
confidence: 99%
“…Wild groundnut species genes that are drought stress involved are discriminated into two groups: (i) genes that are plant cell protectors and act as upstream regulators and (ii) regulatory genes, such as transcription factors, implicated in the ABA pathways [ 146 ]. Tolerance to abiotic stresses has been recorded in A. stenosperma [ 128 ], while Guimarães et al [ 147 ] identified a remarkable number of transcription factors and genes related to drought stress in a peanut ancestor, A. duranencis .…”
Section: The Exploitation Of the Cwrs In Specific Cultivated Speciesmentioning
confidence: 99%
“…Peanut suffers from a narrow genetic base (Kochert et al, 1991) and no longer has access to many genes contained in related wild relatives. However, many genes associated with both biotic and abiotic stressors have been identified (Cason et al, 2020), and gene introgression has successfully been used to move alleles into cultivated peanut and is still one of the best options available to peanut breeders (Cason et al, 2020). An excellent example of this is the resistance to root knot transferred from Arachis cardenasii (Burow et al, 1996;Simpson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%